Binational Human Rights : The U.S.-Mexico Experience - Mueller, Carol McClurg; Simmons, William Paul, 1965- (Book collections on Project MUSE., 2014)
"Mexico ranks highly on many of the measures that have proven significant for creating a positive human rights record, including democratization, good health and life expectancy, and engagement in the global economy. Yet the nation's most vulnerable populations suffer human rights abuses on a large scale, such as gruesome killings in the Mexican drug war, decades of violent feminicide, migrant deaths in the U.S. desert, and the ongoing effects of the failed detention and deportation system in the States. Some atrocities have received extensive and sensational coverage, while others have become routine or simply ignored by national and international media. Binational Human Rights examines both well-known and understudied instances of human rights crises in Mexico, arguing that these abuses must be understood not just within the context of Mexican policies but in relation to the actions or inactions of other nations, particularly the United States."--Publisher description